2016
DOI: 10.15578/ifrj.22.1.2016.17-26
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sub Surface Temperature, Salinity and Chlorophyll to Albacore Tuna Abundance in Indian Ocean

Abstract: The swimming layer is one of the important factors to get maximum catches, especially on tuna longline effort. The vertical abundance of the albacore tuna was investigated based on catch data and 3-DINDESO Ocean Model data, such as sub-surface conditions of sea water potential temperature (Temp), salinity (Sal) and mass concentration of diatoms and flagellates expressed as chlorophyll (Chl) in the Eastern Indian Ocean period 2014-2015. Combining he statistical method of generalized additive model (GAM) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Our analysis showed that the majority of Bigeye tuna angling sets are 34.5 -34.8 psu in Sub_SS. e nding was con rmed by Novianto & Susilo (2016) who stated that Bigeye tuna generally disseminated at a salinity value of 34 psu. In addition, high salinity were believed defer the relocation of Bigeye tuna.…”
Section: Resultsmentioning
confidence: 86%
“…Our analysis showed that the majority of Bigeye tuna angling sets are 34.5 -34.8 psu in Sub_SS. e nding was con rmed by Novianto & Susilo (2016) who stated that Bigeye tuna generally disseminated at a salinity value of 34 psu. In addition, high salinity were believed defer the relocation of Bigeye tuna.…”
Section: Resultsmentioning
confidence: 86%
“…There is a fairly large body of evidence that shows that areas of high CHL‐a concentrate a huge number of marine top predators, including predatory fish (Novianto & Susilo, 2016), cetaceans (Panigada et al, 2008; Gill et al, 2011; Breen et al, 2016) and seabirds (Weimerskirch et al, 2005; Louzao et al, 2012). Moreover, previous studies have succeeded in using CHL‐a as the main explanatory variable in niche models for the Balearic shearwater (Louzao et al, 2006a; Louzao et al, 2012; Araújo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental variables previously investigated for possible effects on the distribution of south Pacific albacore (Briand et al, 2011;Novianto and Susilo, 2016;Erauskin-Extramiana et al, 2019) were included in this study: sea surface temperature (SST, • C), sea surface salinity (SSS, PSU), mixed layer depth (MLD, m), dissolved oxygen concentration under 100 m depth (DO100, mmol L −1 ), and chlorophyll-a concentration (CHL, kg L −1 ). Monthly averaged satellite data [SST, SSS, MLD, DO100, and CHL] from 1997 to 2016 were used to characterize the environmental preferences of south Pacific albacore by using the GAM analysis (see section "Species Distribution Model").…”
Section: Historical and Future Environmental Datamentioning
confidence: 99%
“…In this context, it was appropriate to fit the delta approach which models the probability of encounter of a fish population and the non-zero CPUE when fish are encountered (Pennington, 1983(Pennington, , 1996Lo et al, 1992). Due to the low percentage of zero catches (<10%) of the quarterly 5 • × 5 • aggregated dataset that implying zero inflation was not an issue (Ichinokawa and Brodziak, 2010), we only fit the catch rate model using the log-transformed CPUEs of albacore, with a small constant (10% of the grand mean) added to avoid log-transformation problems (Campbell et al, 1996;Howell and Kobayashi, 2006;Mugo et al, 2010). GAMs were built using the gam function of the "mgcv" package in R-language TABLE 1 | List of IPCC atmosphere-ocean general circulation models where the future environmental variables, including the sea surface temperature (SST, • C), sea surface salinity (SSS, PSU), mixed layer depth (MLD, m), chlorophyll-a concentration (CHL, kg L −1 ), and dissolved oxygen concentration under 100 m depth (DO100, mmol L −1 ), were obtained to generate potential habitat maps of south Pacific albacore under ocean warming scenarios (RCP 4.5 and RCP 8.5).…”
Section: Species Distribution Modelmentioning
confidence: 99%
See 1 more Smart Citation